Conserved and Widespread Expression of piRNA-Like Molecules and PIWI-Like Genes Reveal Dual Functions of Transposon Silencing and Gene Regulation in Pinctada fucata (Mollusca) - Huang, Songqian; Ichikawa, Yuki; Yoshitake, Kazutoshi; Kinoshita, Shigeharu; Asaduzzaman, Md; Omori, Fumito; Maeyama, Kaoru; Nagai, Kiyohito; Watabe, Shugo; Asakawa, Shuichi (Frontiers in Marine Science, 2021)
PIWI proteins and PIWI-interacting RNAs (piRNAs) suppress transposon activity in animals, thus safeguarding the genome from detrimental insertion mutagenesis. Recent studies revealed additional targets and functions of piRNAs in various animals. piRNAs are ubiquitously expressed in somatic tissues of the pearl oyster Pinctada fucata, however, the role of somatic piRNAs has not well characterized. This study reports the PIWI/piRNA pathway, including piRNA biogenesis and piRNA-mediated transposon silencing, and gene regulation in P. fucata. The biogenesis factors of PIWI, Zucchini, and HEN1, which are ubiquitous in somatic and gonadal tissues, were first identified in P. fucata using transcriptome analysis. Bioinformatics analyses suggested that different populations of piRNAs participate in the ping-pong amplification loop in a tissue-specific manner. In addition, a total of 69 piRNA clusters were identified in the genome of P. fucata based on the expression of piRNAs, which contained 26% transposons and enhanced for DNA/Crypton, LINE/CR1, SINE/Deu, and DNA/Academ. The expression patterns of the piRNAs and piRNA clusters in somatic tissues were not substantially different, but varied significantly between the somatic and gonadal tissues. Furthermore, locked-nucleic-acid modified oligonucleotide (LNA-antagonist) was used to silence single piRNA (piRNA0001) expression in P. fucata. Hundreds of endogenous genes were differentially expressed after piRNA silencing in P. fucata. Target prediction showed that some endogenous genes were targeted by piRNA0001, including twelve upregulated and nine downregulated genes after piRNA0001 silencing. The results indicated that piRNAs from somatic tissues may be related to gene regulation, whereas piRNAs from gonadal tissues are more closely associated to transposon silencing. This study will enhance our understanding of the role of piRNAs in mollusks, transposon silencing, and the regulatory function of the PIWI/piRNA pathway on protein-coding genes outside of germ line cells in P. fucata.